Bone-Grafting in Polyostotic Fibrous Dysplasia - Leet, Arabella I; Boyce, Alison M; Ibrahim, Khalda A; Wientroub, Shlomo; Kushner, Harvey; Collins, Michael T (Journal of bone and joint surgery. American volume, 2016)
Polyostotic fibrous dysplasia is a skeletal disease that results from somatic activating mutations in the gene GNAS in skeletal stem cells, leading to proliferation of immature osteogenic cells with replacement of normal marrow and bone with fibro-osseous tissue. Lesions may cause bone deformity or fracture. In the surgical care of polyostotic fibrous dysplasia, the role of grafting and the optimal grafting material are not clear. The purpose of this study was to evaluate the long-term survival of bone-grafting procedures in subjects with polyostotic fibrous dysplasia over time. The operative reports and radiographs of a cohort of subjects with polyostotic fibrous dysplasia followed in a natural history study were reviewed. Twenty-three subjects (mean age at the time of enrollment, thirteen years [range, two to forty years]) with fifty-two bone-grafting procedures had a mean follow-up time of 19.6 years (range, twenty-nine months to forty-seven years). Kaplan-Meier life table estimates, Cox proportional hazard models, and t tests comparing means were performed to assess various aspects of graft survival. Kaplan-Meier curves showed a 50% estimate of survival of 14.5 years. Cox proportional hazards models showed no advantage comparing allograft with autograft or structural with nonstructural graft materials. The mean age of the patients was significantly greater (p < 0.001) in the subgroup of subjects in whom grafts were maintained over time (20.9 years) compared with the subgroup of patients whose grafts were resorbed over time (9.8 years). Bone-grafting, including both allograft and autograft, is of limited value in ablating the lesions of fibrous dysplasia. The expectations of patients and surgeons should include the high probability of graft resorption over time with return of bone characteristics of fibrous dysplasia, particularly in younger patients. This suggests the maintenance of normal bone mechanics with implant support should be the priority of any surgical intervention.